HUMANISTIC AND INFORMATION-TECHNOLOGICAL PARADIGMS OF INFORMATION SOCIETY’S IDEOLOGY IN THE ERA OF GLOBALIZATION AND INFORMATIONAL REVOLUTION - Kyrychenko, Mykola O. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2018)
As an answer to the ideology of information society in the era of globalization and informational revolution, the humanistic and information-technological paradigms used as a conceptual frame due to the new trends of informatization. This article formulates an objective concept of the new humanistic and information-technological paradigms of information society’s ideology that determined by the generalization of theoretical and practical experience of informatization and allows to identify the coordinates of formation the information society’s ideology. The main aim of the article is the conceptualization of humanistic and information-technological paradigms of information society’s ideology in the era of globalization and informational revolution. The modern civilization features that contributes to the formation of the information society’s ideology; place and role of the cognitariate (netocracy) and two models of the information society’s ideology (humanistic and technocratic) are analyzed in the article. Proved the meaning that technocratic way of forming the information society’s ideology has strong support from the side of the economic and political elites. However, there is a threat to become a hostage of technological reality. The humanistic model of information society’s ideology is opposed to the dehumanize technologies for the natural and cultural identity preserving. The scientific novelty: both types of information society’s ideology in the national modern philosophy has not been analyzed yet. Conclusion: isolated information, lack of developed information infrastructure, lack of ideology of the information society, political and socioeconomic conditions that restrain the development of information infrastructure are the reasons that do not allow Ukraine to get the competitive position behind western countries in the development of information and communication technologies.